Application Of Endomycorrhizal Spores, Compost, And Trichoderma Spp. Increased Growth Of Cacao Seedlings (Theobroma cacao L.) - Akbar, Tadzkia Hanifah; Proborini, Meitini Wahyuni; Defiani, Made Ria (Metamorfosa: Journal of Biological Sciences, 2022)
Quality of cacao seedlings ( Theobroma cacao L.) is one of the effort to maintain agroforestry and forest functions. This study aimed to identify the effects of the endomycorrhizal spores, compost, and Trichoderma spp. for cacao seedlings and to investigate the best concentration of media combinatioins on growth of  cacao seedlings. The study was carried out in plant taxonomy laboratory (mycology) and the green house of Suwung Permanent Nursery, BPDASHL. Treatments were set up on RCBD (Randomized Complete Block  Design) with five treatment combinations and 5 replications and 3 units of experiment. The first treatment was application of  sterile soil only (negative control), the second treatment was with sterile soil+10 g of compost+10mL of Trichoderma spp (positive control), the third treatment was sterile soil+100 spore of  endomycorrhizal Glomus sp. +10 g of compost+10mL of Trichoderma spp, the fourth treatment was with sterile soil+150 spore of  endomycorrhizal Glomus sp. +10 g of compost+10mL of Trichoderma spp, and the fifith treatment was with sterile soil+200 spore of  endomycorrhizal Glomus sp. +10 g of compost+10mL of Trichoderma spp. The result showed that combination of the fifith treatment (sterile soil+200 spore of  endomycorrhizal Glomus sp. +10 g of compost+ 10mL of Trichoderma spp.) was the best combination cacao seedlings for plant heights (29,03 cm), plant dry weight  (3,55 g), root dry weight (1,83 g), and the percentage of endomycorrhizal colonization (6,33%). Keyword: Green house, Glomus sp., agroforestry, colonization percentage